Margaret Fuller’s conversations: Speaking as revision and feminist resistance - Quawas, Rula (Adam Mickiewicz University, 2012)
Conversation as a means to social, intellectual, and spiritual self-culture was advocated during the American Romantic period by members of the Transcendental movement. Margaret Fuller was a transcendental conversationalist who challenged the theoretical setting and practice of selfculture, remedied the gap in it about concepts of womanhood that were imposed by the culture of the time and that attempted to determine women’s place in the symbolic order, and placed an emphasis on self-knowledge, whatever the subject matter. She came to represent a rhetoric whose aim was to foster community, moral truths, ethical actions, and feminist resistance. Fuller fully subscribed to the idea of the revelatory power in conversation and provided women with an opportunity to develop the intellectual rigor necessary to establish their own identities in the world: public or private. Through her weekly conversations for Boston women, held from 1839 through 1844, she used conversation or speaking as revision to explore philosophical, aesthetic, and sociocultural questions and supplied access to education from which women were excluded.